Marginalisasi dan Revitalisasi Wayang Kulit Parwa di Kabupaten Gianyar pada Era Globalisasi - I Made Yudabakti (Universitas Udayana, 2016)
On this globalization era many local arts have faced processes of marginalization, including parwa shadow puppet as can be seen in Gianyar Regency, Bali. This article studies about the marginalization of parwa shadow puppet (WKP) in Gianyar Regency. The study based on observation of this specific WKP in the period of a decade, 2000 until the year 2010. In addition of observation, data for the study were collected through interview and desk research. The research shows that in the last ten years, the popularity of WKP has declined marked by the decrease in number of audiences and performance schedule of all WKP puppeteer including that performances for religious activity. Marginalization of WKP are caused by an internal and external factors. Internal factor consisted of decreasing society fascination watch on the WKP, declining of puppeteer creativity, weaknesses in the policy of traditional institutions, and the lack of support from the government. The external factor included the obscure future of WKP, people are more intearested with aspects of an entertainment than moral teaching of the performance, the increasing influence of global arts, and the availability of modern entertainment amusement sources. The research also shows that amidst the strong marginalization phenomena of life of the WKP in the same time there has been efforts to preserve the WKP in Gianyar.